Analysis of the Impact of Technological Development and Community Culture on Teachers' Teaching Methods at Ecayo Yamaha Music School - Dunan, Hendri; Gabe Sahata Sihite, Christman (Lafadz Jaya Publisher, 2024)
Ecayo Yamaha Music School is the largest music school in Lampung with international competence.Based on the passion and commitment to provide professional and quality music learning, this music school focuses on providing a fun and high standard music learning experience.Nowadays, we have entered an era where technology is developing very rapidly. The rapid development of technology has become the main driver of change in all aspects of human life, especially in the educational aspect. In this era of globalization, technological advances not only influence the industrial and economic fields, but also have a significant impact on people's thought patterns, social interactions and paradigms of cultural life. The researcher made initial observations and there were problems, namely the monotonous way of teaching because the teachers only followed the curriculum, there was a lack of variety in learning methods, such as not really caring about methods that suited the students, learning methods such as being given material, giving examples, and practicing and repeating. That way, students will feel bored and have difficulty understanding the material. The aim of the researcher is to analyze the impact of technological developments and societal culture on the way teachers teach at Ecayo Yamaha Music School. In this study, qualitative methods were used, the reviewer collected data using an interview system. The results of the analysis show that technological developments and societal culture have an impact on the way teachers teach.